Phyto-synthesis of silver nanoparticles from Plumeria pudica leaf extract and its application in anti-cancerous activity - Sumit K. Shrivastava; Asita Kulshreshtha; Rajesh K. Gangwar; Shikha Srivastava; Abhishek P. Tiwari; Santpal Singh; Saurabh Kumar; Shama Parveen; Monisha Banerjee; Dhirendra K. Chaudhary (Journal of Experimental Nanoscience)
In this study, we have developed an environment friendly and novel approach for the synthesis of silver nanoparticles utilising plumeria pudica leaf extract. In this technique, the leaf extract was employed as both a reducing agent for the reduction of a silver nitrate (AgNO3) solution and a capping agent, leading to the synthesis of silver nanoparticles (Ag NPs). The outcomes of these analyses revealed an average particle size of ∼19 nm as determined by SEM, while XRD measurements indicated a crystalline domain size of ∼12 nm and a lattice parameter of approximately 4.087467 Å. Furthermore, the anti-cancer potential of the synthesised silver nanoparticles was evaluated, unveiling an IC50 value of around 28 µM. This suggests that the introduced silver nanoparticles may have triggered apoptosis, consequently inducing cell death. These findings underscore the potential of utilising environmentally benign silver nanoparticles in lung cancer chemotherapy.